A Computer Output Microfilm Serials List for Patron Use - Saffady, William (Information Technology and Libraries, 1974)
Library literature generally assumes that COM is better suited to staff rather than patron use applications. This paper describes a COM serials holdings list intended for patron use. The application and conversion from paper to COM are described. Emphasis is placed on the selection of an appropriate microformat and easily operable viewing equipment as conditions of success for patron use.